SINGLE BULB GARLIC (Allium sativum) EXTRACT IMPROVE SPERM QUALITY IN HYPERLIPIDEMIA MALE MICE MODEL - Qadariah, Nosi; Lestari, Sri Rahayu; Rohman, Fatchur (Jurnal Kedokteran Hewan, 2020)
The aim of this research was to find out the influence of single bulb garlic on sperm quality improvement in hyperlipidemia model of male mice. Male mice (Balb-C, 12 weeks, bw 215 g) were given high fat diet for 45 days until their body weight achieved 455 g. The mice were then divided into six groups. The mice in the first group (control group (N)) was fed with 7 g higrow pokphan 551 per day. The mice in the second group (control negative group) was fed with 7 g high fat diet (HFD), while the mice in the third group (control positive group) were treated with statin at dose of 0.91 mg. The mice in groups 4, 5, and 6 were treated with single bulb garlic extract at dose of 125 mg/kg bw, 250 mg/kg bw, and 500 mg/kg bw, respectively. On the 31st day, the male were dissected and cauda epididymis was taken and chopped in a sterile phosphat buffer saline (PBS) and observation conducted on sperm quality consisted of sperm count, sperm motility and sperm normality. The results indicated a significant increase in sperm count, motility and normality in mice treated with single bulb garlic extract at dose of 250 mg/kg bw.